Cumulative Live Birth Rates in Low Prognosis Patients According to the POSEIDON Criteria: An Analysis of 26,697 Cycles of in vitro Fertilization/Intracytoplasmic Sperm Injection - Li, Yuan; Li, Xiaofeng; Yang, Xiaoyi; Cai, Sufen; Lu, Guangxiu; Lin, Ge; Humaidan, Peter; Gong, Fei (Frontiers in Endocrinology, 2019)
Objective: The POSEIDON criteria are used to stratify patients with low prognosis after assisted reproductive technology (ART) treatment. Since its introduction, there has been no large study about the prognosis of the POSEIDON population. We used the POSEIDON criteria in Chinese women who underwent repeated ART treatment and analyzed the association between POSEIDON criteria and the cumulative live-birth rate (CLBR). Methods: This was a retrospective cohort study of 62,749 women (97,388 cycles) who underwent ART treatment at the Reproductive and Genetic Hospital of CITIC-XIANGYA between January 2014 and June 2017. Among them, 19,781 (31.52%) women fulfilled the POSEIDON criteria, including 26,697 cycles. The optimal and conservative CLBRs within a complete IVF/ICSI treatment cycle were calculated, as well as the CLBRs following repeated ovarian stimulation cycles. Results: In POSEIDON groups 1, 2, 3, and 4, the optimal and conservative CLBRs of three complete consecutive in vitro fertilization (IVF)/intracytoplasmic sperm injection (ICSI) cycles were 83.87 and 66.06%, 53.67 and 37.72%, 44.24 and 27.98%, and 14.20 and 9.68%, respectively. The POSEIDON stratification [group 2: odds ratio (OR) = 2.319, 95% confidence interval (CI): 2.131–2.525, P < 0.001; group 3: OR = 1.356, 95% CI: 1.005–1.828, P = 0.046; group 4: OR = 3.525, 95% CI: 2.774–4.479, P < 0.001; all vs. group 1] and ovarian stimulation protocol [gonadotropin-releasing hormone (GnRH) antagonist protocol: OR = 1.856, 95% CI: 1.640–2.100, P < 0.001; other protocols: OR = 1.651, 95% CI: 1.155–2.361, P = 0.006; both vs. long GnRH agonist protocol] were associated with live birth in the first stimulation cycle. For the second stimulation cycle, the POSEIDON stratification (except POSEIDON group 3) and ovarian stimulation protocol were associated with live birth. A change in ovarian stimulation protocol was not associated with an improvement in the live birth rate. Conclusions: More than 30% of women who undergo IVF/ICSI treatment may be classified as low prognosis. Different reproductive outcomes were observed among the four POSEIDON groups. The most optimal outcomes after three successive cycles of IVF/ICSI treatment were observed in groups 1, 2, and 3.